Psychometric properties and clinical correlates of the Frontal Behaviour Inventory in progressive supranuclear palsy: data from the PSP-NET - Cappiello, Arianna; Cuoco, Sofia; De Micco, Rosa; Satolli, Sara; Di Biasio, Francesca; Markushi, Tiziana Benzi; Sambati, Luisa; Pilotto, Andrea; Costanzo, Matteo; Longo, Chiara; Schirinzi, Tommaso; Del Prete, Eleonora; et al. (Neurological sciences, 2025)
Objectives Neuropsychiatric symptoms, such as apathy, disinhibition and irritability, are common in Progressive Supranuclear Palsy (PSP). The Frontal Behaviour Inventory (FBI) is a useful instrument for the evaluation of behavioural disorders in neurodegenerative diseases. The main goal of the present study was to explore the psychometric properties of the FBI in PSP. Design, setting and participants FBI was administered to the PSP-NET cohort including Italian patients diagnosed according to the Movement Disorder Society criteria. Patients underwent a clinical interview, a motor evaluation, extensive cognitive and behavioural testing. Results Two hundred and eight subjects were included in this study. The internal consistency was high (Cronbach’s alpha = 0.868) and no improvement of this value was noted upon removal of any item. FBI showed also good acceptability, reliability and validity. The standard error of measurement (SEM) value for FBI total score was 0.169 [SEM = SD √ (1 – Cronbach’s alpha)]. Factor analysis indicated a five-factor structure: Apathy , Behavioural disorders , Impulsivity , Motor and speech frontal behaviour and Executive disorders that explained the 54.92% of the total variance. Linear regression analysis showed that global cognitive impairment significantly affects both Apathy and Motor and speech frontal behaviour factors. Conclusions In conclusion, FBI is a reliable and valid tool for the assessment of neuropsychiatric symptoms in PSP, despite some constructs, such as euphoria and irritability, are better measured by the NPI. Two third of the cohort was represented by Richardson’s syndrome, thus our data are mainly applicable to such common phenotype. Such data are useful in both clinical and research settings to plan adequate therapeutic interventions and to improve the quality of life of PSP patients and their caregivers.